REACTION OF ABNORMAL RETURN AND TRADING VOLUME ACTIVITY BEFORE AND AFTER THE ELECTION OF THE PRESIDENT OF THE REPUBLIC OF INDONESIA IN 2019 - Rizki Chahyadi Paputungan; Abdul Rahman Mus; Mursalim Mursalim (Jurnal Ilmu Manajemen Profitability, 2021)
This research aims to analyze abnormal return and trading volume activity in the time before and after the 2019 Presidential election. Especially in state-owned enterprises that are included in the IDX BUMN 20 index in IDX. This research is a quantitative research using the event study method with an observation time of 7 days before and 7 days after the 2019 Presidential election. Using secondary data in the form of stock prices and trading volumes. The results showed that: (1) based on the results of the paired sample test against abnormal return during the period of event, it was found that there was no difference in abnormal return before and after the presidential election; (2) from the Wilcoxon-Signed Rank test results there is a significant difference in trading volume activity before and after the presidential election of the Republic of Indonesia